Analisis Wacana Kritis (AWK) Jurnalisme Berperspektif Gender Pada Artikel Pemilu 2024 di Konde.co - Ayu Adriyani; AB Sarca Putera; Eda Elysia; Ilma Wulandari; Muhammad Al Fikran Firlian (Universitas Medan Area, 2026)
This article addresses the lack of a gender perspective in the media. This study employs a qualitative approach, using a case study framework, to analyse news articles on women’s issues and the general election published on Konde.co. These articles were analyzed using Sara Mills’ critical discourse analysis model. This study aims to analyse how Konde.co practices gender-sensitive journalism, specifically in 11 articles covering women’s issues and the 2024 general election. Most previous research has focused on gender bias in mainstream media. Thus, this study seeks to fill that research gap with a clear novelty: a focus on the portrayal and narratives of women during the 2024 general election on Konde.co, as well as an analysis of gender bias in alternative media in practical political reporting. This study concludes that, in the articles examined, Konde.co portrays women as active subjects with the authority to narrate their experiences and perspectives. Women are also depicted as actors capable of conducting critical analyses of various issues. The texts also position readers as parties who are guided to understand and support women’s experiences. Theoretically, this research contributes to the development of communication studies, particularly regarding gender representation and the role of alternative media. The practical implication of this study is to promote fairer and more gender-sensitive journalism practices in Indonesia.